Calculation of Integral Indicators of the Metabolic Status and Filtration Function of Kidneys in Patients with a Combat Mine-Explosive Injury who Lost Significant Body Weight due to Limb Amputation - Sydorova, Nataliia; Kazmirchuk, Kateryna; Kolisnyk, Oleh; Tsaralunha, Vira; Kobirnichenko, Yuliia; Sydorova, Liudmyla (Acta medica Lituanica, 2025)
Background: The aim of this retrospective cohort study was to investigate the possibility of optimizing the calculation of integral indicators of the metabolic status and filtration function of the kidneys in patients with combat mine-explosive injuries who have lost significant body weight due to limb amputation.Methods: Data from 81 servicemen (all males) with combat mine-explosive limb injuries, including those with isolated severe limb injuries (Group 1, n=34) or traumatic amputations (Group 2, n=47), were analyzed. We assessed demographic indicators and the glomerular filtration rate (GFR), calculated according to the generally accepted formulas with correction for lost body parts in the amputees.Results: The proportion of amputees with obesity as measured by the body mass index in Group 2 without correction for the lost body parts was significantly lower than that in Group 1 and Group 2 adjusted for the lost body parts (2.12% versus 17.65% and 21.28%, respectively, p
Keywords: limb amputation; body mass index; correction; glomerular filtration rate; hyperfiltration; traumatic amputation; combat trauma